Construction of an Integral Manifold of a Multifrequency Oscillation System with Fixed Times of Pulse Action - Petryshyn, R. I.; Samoilenko, A. M.; Sopronyuk Т. M. (Ukrains’kyi Matematychnyi Zhurnal, 2003)
We determine a class of multifrequency resonance systems with pulse action for which an integral manifold exists. We construct a function that determines a discontinuous integral manifold and investigate its properties.